Wybrane aspekty funkcjonowania instytucji ubezpieczeniowych na rynku finansowym w Polsce - Jóźwicki, Rafał (Selected Aspects of the Activity of the Insurance Companies in the Financial Market in Poland, 2008)
Insurance companies are one of the most important investors in the financial market. These companies form contracts with their clients and pay claims, so they must conduct proper asset management. The main goal of this paper is to examine the financial assets of insurance companies between 2002 and 2006. The author took into consideration data from life and non-life sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 132-138